Nutrient Partitioning and Stoichiometry in Unburnt Sugarcane Ratoon at Varying Yield Levels - Leite, José M.; Ciampitti, Ignacio A.; Mariano, Eduardo; Vieira-Megda, Michele X.; Trivelin, Paulo C. O. (Frontiers in Plant Science, 2016)
Unraveling nutrient imbalances in contemporary agriculture is a research priority to improve whenever possible yield and nutrient use efficiency in sugarcane (Saccharum spp.) systems while minimizing the costs of cultivation (e.g., use of fertilizers) and environmental concerns. The main goal of this study was therefore to investigate biomass and nutrient [nitrogen (N), phosphorus (P), and potassium (K)] content, partitioning, stoichiometry and internal efficiencies in sugarcane ratoon at varying yield levels. Three sites were established on highly weathered tropical soils located in the Southeast region of Brazil. At all sites, seasonal biomass and nutrient uptake patterns were synthesized from four sampling times taken throughout the sugarcane ratoon season. At all sites, in-season nutrient partitioning (in diverse plant components), internal efficiencies (yield to nutrient content ratio) and nutrient ratios (N:P and N:K) were determined at harvesting. Sugarcane exhibited three distinct phases of plant growth, as follows: lag, exponential-linear, and stationary. Across sites, nutrient requirement per unit of yield was 1.4 kg N, 0.24 kg P, and 2.7 kg K per Mg of stalk produced, but nutrient removal varied with soil nutrient status (based on soil plus fertilizer nutrient supply) and crop demand (potential yield). Dry leaves had lower nutrient content (N, P, and K) and broader N:P and N:K ratios when compared with tops and stalks plant fractions. Greater sugarcane yield and narrowed N:P ratio (6:1) were verified for tops of sugarcane when increasing both N and P content. High-yielding sugarcane systems were related to higher nutrient content and more balanced N:P (6:1) and N:K (0.5:1) ratios.